Moving Target Defense Creating Asymmetric Uncertainty for Cyber Threats - Jajodia, Sushil; Ghosh, Anup K.; Swarup, Vipin; Wang, Cliff; Wang, X. Sean.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Moving Target Defense: Creating Asymmetric Uncertainty for Cyber Threats was developed by a group of leading researchers. It describes the fundamental challenges facing the research community and identifies new promising solution paths. Moving Target Defense which is motivated by the asymmetric costs borne by cyber defenders takes an advantage afforded to attackers and reverses it to advantage defenders. Moving Target Defense is enabled by technical trends in recent years, including virtualization and workload migration on commodity systems, widespread and redundant network connectivity, instruction set and address space layout randomization, just-in-time compilers, among other techniques. However, many challenging research problems remain to be solved, such as the security of virtualization infrastructures, secure and resilient techniques to move systems within a virtualized environment, automatic diversification techniques, automated ways to dynamically change and manage the configurations of systems and networks, quantification of security improvement, potential degradation and more. Moving Target Defense: Creating Asymmetric Uncertainty for Cyber Threats is designed for advanced -level students and researchers focused on computer science, and as a secondary text book or reference. Professionals working in this field will also find this book valuable.
A Formal Model for a System$1 (Bs Attack Surface -- Effectiveness of Moving Target Defenses -- Global ISR: Toward a Comprehensive Defense Against -- Compiler-Generated Software Diversity -- Symbiotes and defensive Mutualism: Moving Target Defense -- Manipulating Program Functionality to Eliminate Security -- End-to-End Software Diversification of Internet Services -- Introducing Diversity and Uncertainty to Create Moving Attack -- Toward Network Configuration Randomization for Moving Target Defense -- Configuration Management Security in Data Center Environments.s
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information systems; Computer Science; Systems and Data Security; Data Encryption; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Systems and Communication Service